A TRANSLATION INTO ENGLISH OF KHALIL I. AL-FUZAI’S “EURHYTHMICS ON THE PAVEMENT OF DANGER” - Dohal, Gassim H. (International Journal of Research -GRANTHAALAYAH, 2021)
Khalil I. Al-Fuzai (1940-) is a man of letters from Saudi Arabia who published few collections of stories. In these stories he tries to introduce his characters in a simple, frank way (see Dohal 2013). One of these stories is “Eurhythmics on the Pavement of Danger.” Here he addresses the issue of journalism. I chose to translate this story for it is a good sample of how Al-Fuzai has connected between journalism and war (see other themes he addresses in Dohal, 2013, 2018 & 2019). Furthermore, it presents some aspects what has happened in 1991; this story has a part of history.